WSe2 few layers with enzyme mimic activity for high-sensitive and high-selective visual detection of glucose. Issue 32 (8th August 2017) - Chen, T. M.; Wu, X. J.; Wang, J. X.; Yang, G. W.
Abstract : We demonstrate that WSe2 nanosheets possess intrinsic enzyme mimic activity, and a platform of WSe2 nanosheets was constructed to detect glucose concentration, which showed high-sensitive and high-selective. Abstract : As one of the transition metal dichalcogenide materials, WSe2 in the form of a few layers (nanosheets) have received much attention due to their unique physical, optical and electrical properties. Herein, we demonstrate that WSe2 nanosheets possess intrinsic enzyme mimic activity. Under acidic conditions, they exhibit pronounced peroxidase-like property. The Michaelis–Menten kinetics indicate that the catalytic activity of WSe2 nanosheets is comparable to that of horseradish peroxidase. Based on the color reaction, a platform of WSe2 nanosheets was constructed to detect glucose concentration and it showed high sensitivity and high selectivity, which means that WSe2 nanosheets with peroxidase-like property can be used to develop a highly sensitive and selective colorimetric method for glucose detection. Moreover, due to the electron-transferring and antioxidant properties of WSe2 few layers, the peroxidase-like catalysis is proposed. These findings pave the way for further application of WSe2 nanosheets in nano-biomedicine.